Identification of resistance to rust (Uromyces appendiculatus) and powdery mildew (Erysiphe diffusa) in Portuguese common bean germplasm. Issue 6 (4th September 2013) - Leitão, Susana T.; Almeida, Nuno F.; Moral, Ana; Rubiales, Diego; Vaz Patto, Maria Carlota; Link, W.
Abstract Portugal has a diverse common bean germplasm, which is still grown in farmers' fields. In this work, we searched for resistance to rust (Uromyces appendiculatus) and powdery mildew (Erysiphe diffusa) in a representative collection of the Portuguese common bean germplasm. Despite many accessions depicting intermediate levels of resistance when compared to the susceptible check, 24 and 13 accessions showed low levels of infection, in spite of a compatible interaction (disease severity (DS) values lower than 5% and infection type (IT) of 4), to rust and powdery mildew, respectively, indicative of partial resistance. Moreover, a resistant reaction was observed in 11 accessions when inoculated with powdery mildew (IT = 0–1) and in additional 11 accessions (one in common) when inoculated with rust (IT = 0–2). The levels of resistance found in this report anticipate great potential of the Portuguese national germplasm, recently reported as genetically closer to the Andean common bean gene pool, for disease resistance breeding of this important crop.